Enhancing Learners’ Motivation and Speaking Skill through Cooperative Learning Activities - CHELBI, Rym Ghosn El Bel (Journal of Human Sciences, 2016)
The present research aims at investigating EFL learners’ motivation and English speaking skill development through the implementation of Cooperative Learning activities at the Department of Letters and English at Constantine University, with a sample of third year Didactics. In order to investigate the relationship between the three variables, we first conducted, at the very beginning of our study, a pre questionnaire that was administered to both of the experimental and the control groups, in order to know the students’ views concerning the Oral Expression module and the idea of working in groups. After that, we conducted a pre test for both groups to test the students’ level. Next, a six-week teaching experiment was conducted through the implementation of Cooperative Learning activities with the experimental group and the use of individualistic type of learning with the control group. At the end of the treatment, we administered a post test to the experimental and the control groups. The comparison of the results provided by the pre and post tests aims at determining the effect that the Cooperative Learning activities has on the students of the experimental group, as contrasted with the students of the control group who performed the tasks individually. At last, a post questionnaire was administered in the end of the experiment to the experimental group, so as to survey to what extent the Cooperative Learning activities could be useful in bolstering up the learners’ motivation, and developing their speaking skill. Additionally, a questionnaire was administered to Oral Expression teachers at the department of Letters and Languages at the University of Constantine, with the intention of discerning their assumptions and points of views regarding the effects of Cooperative Learning activities on students’ motivation and speaking skilldevelopment. Overall, the comparison of the pre and post tests’ results of both groups revealed that the students who worked cooperatively to perform the tasks assigned to them outscored the students who worked individually to solve a given task. These findings support our hypotheses, and are in the direction of many studies which emphasize that Cooperative Learning activities act as a bridge between motivation and speaking skill development.